Individual Measurement anduse of water in Residential Buildings - Souza Mendes, Andressa; Thábatta Xavier Almeida, Thyara; Aguiar Santos, Vanderson (Revista Desenvolvimento Social, 2020)
The problem of pollution and water scarcity, related to poor resource utilization, leads to high demand for alternatives to solve it. What much has been heard is that the individualization of water consumption in residential buildings has become a very effective method to combat waste in these environments. With this adoption, each consumer unit will have an individual water meter, whose owner will just assume the expense of consumption, not more spending other residents of the building and therefore have a motivation to avoid wasting water. In this context the studies on the individual water metering in buildings located in the city of Montes Claros, Minas Gerais, making a comparative consumption produced in residential buildings that use the global measurement or individualized measurement. To achieve the research objectives the steps followed were: search along liquidators and residents of data related to water consumption in selected buildings, questionnaires and data analysis for possible conclusions, if the individual measurement actually works as an important tool for the control and reduction of water consumption.